"Evaluation of different dietary oil sources on growth performance and nutrient utilization of Clarias gariepinus juveniles " (2011)
The reported decrease in wild fish stocks has made the replacement of Fish Oil (FO)/codliver oil in aquaculture a priority. The use of vegetable oils (VOs), with lower cost, larger and wider supplies may be a good substitute for FO. The effects of total replacement of cod liver oil (CLO) with VOs, oil palm seed (OPS), Ugwu seed oil (USO)/pumpkin seed oil, soya bean oil (SBO), almond seed oil (ASO)) and a composite of all the VOs referred to as COs on growth performance and nutrient utilization of Clarias gariepinus juveniles was investigated for 12- weeks. Each diet contained 45% CP fed to triplicate groups of 15 juveniles, with initial mean weight 22.82 ± 0.30 g and mean length 15.45 ± 0.04 cm. Fish fed OPS based diet had significantly (P ? 0.05) the highest body weight gain (126.34 ± 25.27 g), followed by USO (110.63 ± 15.48). The highest survival rates of (100%) were in USO and Cos but (97.77%) in ASO and CLO (Control) based diets. Significant differences at (P ? 0.05) were observed in carcass CP of fish fed OPS based diets ( 48.09 ± 1.40 g) compared with the CLO’s (44.86 ± 0.35 g).This research shows evidence that OPS and USO can effectively replace FO in diets of C. gariepinus.